2014
DOI: 10.1111/jonm.12228
|View full text |Cite
|
Sign up to set email alerts
|

Registered nurses' experiences of rewarding in a Finnish University Hospital - an interview study

Abstract: It is important to listen to nurses' experiences of rewarding because it enables nurse managers to maintain and increase the attractiveness of nursing and health care work in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 30 publications
(134 reference statements)
2
18
1
Order By: Relevance
“…, Seitovirta et al . ). Empirical studies in various sectors have demonstrated clear links between rewards and favourable employee outcomes, such as job satisfaction and motivation at work (e.g., El‐Jardali et al .…”
Section: Introductionmentioning
confidence: 97%
“…, Seitovirta et al . ). Empirical studies in various sectors have demonstrated clear links between rewards and favourable employee outcomes, such as job satisfaction and motivation at work (e.g., El‐Jardali et al .…”
Section: Introductionmentioning
confidence: 97%
“…Rewarding should to be a part of everyday leadership. Few rewarding words, like feedback, may influence to RNs very positive way (De Gieter et al, 2010;Seitovirta et al, 2014). Especially, psychological rewards are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (Eneh et al, 2012;Kvist et al, 2013;Seitovirta, Partanen, Vehviläinen-Julkunen, & Kvist, 2014) have found that nurses believe their rewards are insufficient, and nurse managers should recognize that both financial and psychological rewards are essential for F I G U R E 1 The structure of nursing leadership in Finnish hospital settings. CNO denotes a chief nursing officer and RN a registered nurse motivating nursing staff (De Gieter, Cooman, Pepermaion, & Jegers, 2010;Seitovirta et al, 2014). Nurse managers should offer diverse rewards whenever possible and try to maximize nurses' well-being, motivation and job satisfaction (Seitovirta et al, 2014).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 2 more Smart Citations